THE EFFORTS OF THE KJRI KOTA KINABALAU IN PROTECTING TKI INVOLVED IN THE CASE OF DRUG ABUSE (DADAH) IN 2018-2020 - Sari, Dita Indah; Damayanti, Christy; Dipokusumo, GPH. (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The purpose of this study is to explain and analyze the efforts of the Indonesian Consulate General in Kota Kinabalu to provide protection for migrant workers who are involved in drug abuse cases (dadah) in 2018-2020. This research was studied using diplomacy protection theory and bilateral relations theory. The purpose of this study was to determine the form of protection provided by the KJRI Kota Kinabalu for TKI who were involved in drug abuse cases (dadah). The research method used is a qualitative descriptive research method with primary data collection and secondary data. Primary data collection was carried out by conducting interviews with the KJRI Kota Kinabalu staff, then secondary data was carried out by collecting documents obtained from various reference sources of books, libraries or online information then sorted and focused and described descriptively. From the data collection the researchers concluded that the bilateral relationship which exists between Indonesia and Sabah, Malaysia plays a very important role in the protective diplomacy practice of the KJRI Kota Kinabalu in providing protection for migrant workers who are involved in drug abuse cases (dadah) . The forms of protection provided by the KJRI Kota Kinabalu for migrant workers who are involved in drug abuse cases (dadah) are technical protection, juridical protection, and political protection. Keywords: KJRI Kota Kinabalu, Protection Diplomacy, TKI, Narcotics.